IMPLEMENTASI DAN ANALISIS QoS PADA JARINGAN MPLS-VPN BERBASIS MPLS-TE MENGGUNAKAN ROUTING PROTOKOL OSPF - Kusuma, Yusuf Budi; Jusak, Jusak; Triwidyastuti, Yosefine (Journal of Control and Network Systems (JCONES), 2016)
Demand for Internet services such as private network, secure network and data transfer speed has raised challenges within the network. To cope with the demand of speed access in the network, in the last decade MPLS technology has emerged. The MPLS is developed one of which to support VPN and MPLS-Traffic engginering. MPLS-VPN is a VPN who utilize MPLS technology to improve VPN capabilities in terms of quality QoS.Traffic Engineering in MPLS is process of selecting a data channel traffic to balance the traffic load on the various lines and points on the network as well as managing traffic better network using alternate pathways. In this research, we will compare the performance characteristics of the MPLS-TE and MPLS-VPN. The research is divided into four steps. Step one is MPLS-VPN network configuration and MPLS-TE network configuration. Step two is downloading data from the server to the PC 1 and PC2. Step 3 is capturing data traffic using wireshark software, and Step four is testing and calculations of data to determine the QoS quality results calculated to be a reference to draw conclusions. Based on the results of research and analysis on the simulated network of the MPLS-VPN and the MPLS-TE, is evidence that the MPLS-TE is more reliable than the MPLS-VPN. The analysis was tested using QoS parameters such as latency (delay), jitter, throughput and packet loss. Keywords: MPLS-TE, Quality of Service, Mikrotik